Odpowiedź:
[tex]m_{1}= \frac{7-\sqrt{41} }{-2}[/tex] , [tex]m_{2}= \frac{7+\sqrt{41} }{-2}[/tex]
Szczegółowe wyjaśnienie:
[tex]a_{1} = m^{2}-2 , a_{2} = - 2 , a_{3} = 7m[/tex]
Różnicę w ciągu arytmetycznym obliczam w następujący sposób:
r = [tex]a_{2} - a_{1}[/tex] = [tex]a_{3}-a_{2}[/tex]
- 2 - ( [tex]m^{2}-2[/tex] ) = 7m - ( -2 )
- 2 - [tex]m^{2}+2[/tex] = 7m + 2
- [tex]m^{2}[/tex] - 7m - 2 = 0
Δ = 49 - 8 = 41
[tex]m_{1}= \frac{7-\sqrt{41} }{-2}[/tex] , [tex]m_{2}= \frac{7+\sqrt{41} }{-2}[/tex]